ANALISIS PEMASARAN OTAK-OTAK JUMBO IKAN TENGGIRI PADA UMKM PERMAI SARI KABUPATEN BANDUNG - Junianto, Junianto; Hidayati, Salmaa Ishma; Nanang, Nanang; Febrianti, Risma Melati; Reza, Mohamad (Fakultas Ekonomi dan Bisnis, 2024)
Permai Sari’s MSME, which is located in the Kopo complex, is a micro, small and medium enterprise that sells products in the field of fish processing, namely grilled fish cake made from mackerel fish. Carrying out marketing analysis aims to find out how management and social processes occur in Permai Sari’s MSME. This research method uses a survey method. Sampling used purposive sampling. The data collected is primary data from interviews and secondary data taken from journals, books or other libraries. The results of this research show that the business of grilled fish cake made from mackerel fish obtained an added value of IDR 47,000/kg of raw material. With a profit of IDR 41,390/kg. Permai Sari's MSME competitors in terms of selling otak-otak products are street vendors who don't sell every day. Determining product prices uses cost-plus pricing which aims to make a profit. The promotional methods used are word of mouth and through applications on the internet. Distribution of otak-otak products by leaving them in stores and selling directly to consumers. Analysis of product production using forecasting methods.